2019
DOI: 10.1021/acsenergylett.9b01517
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Activated Electrolysis for Cogeneration of Nitric Oxide and Hydrogen from Water and Nitrogen

Abstract: With increasing global interest in renewable energy technology in the backdrop of climate change, storage of electrical energy has become particularly relevant. Most sustainable technologies (e.g. wind, solar) produce electricity intermittently. Thus, converting electrical energy and base molecules (i.e. H2O, N2) into energy rich ones (e.g. H2, NH3) or chemical feedstock (e.g. NO) is of paramount importance. While H2O splitting is compatible with renewable electricity, N2 fixation is currently dominated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…The results from this study can serve as a benchmark for designing multi‐reaction plasma reactors. One such reactor has been developed recently, which performs water splitting by electrochemical catalysis at atmospheric pressure and uses the generated oxygen in‐situ for NO synthesis in an ICP‐RF reactor operating at vacuum pressures …”
Section: Resultsmentioning
confidence: 99%
“…The results from this study can serve as a benchmark for designing multi‐reaction plasma reactors. One such reactor has been developed recently, which performs water splitting by electrochemical catalysis at atmospheric pressure and uses the generated oxygen in‐situ for NO synthesis in an ICP‐RF reactor operating at vacuum pressures …”
Section: Resultsmentioning
confidence: 99%
“…Research in this scientific field has revealed great potential and progress into using plasma technology to enable endothermic chemical reactions at low reactor temperatures, to improve the properties of catalysts and to synthesize renewable energy materials from greenhouse gases [4, 13 14]. So far different types of plasma technology [16][17][18][19][20][21][22][23][24][25][26] with or without catalysts have been tested on their performance compared to the traditionally thermal chemical processes. Especially a lot of work has been done on Dielectric Barrier Discharge (DBD) generated plasma to dissociate CO2.…”
Section: Introductionmentioning
confidence: 99%
“…The N 2 -O 2 plasma is generated in the area near the coil and activated species flow toward the heating mantle, which is kept at 873 K. 21 to 10 −2 . Also reported is the thermodynamic equilibrium production of NO at 873 K. NO production at zero plasma power (i.e.…”
Section: Plasma-catalytic N 2 Oxidation Experimentsmentioning
confidence: 99%